The effect of an ambidextrous supply chain strategy on combinative competitive capabilities and business performance - Kristal, Mehmet Murat; Huang, Xiaowen; Roth, Aleda V. (Journal of Operations Management, 2010)
AbstractThis study investigates the influence of an ambidextrous supply chain strategy on manufacturers’ combinative competitive capabilities – the ability to excel simultaneously on competitive capabilities of quality, delivery, flexibility, and cost – and, in turn, on business performance. Drawing upon March's (1991) notions of exploration and exploitation, an ambidextrous supply chain strategy is conceptualized as a simultaneous pursuit of both explorative and exploitative supply chain practices. We operationalize this concept as a second‐order latent construct that captures the co‐variation between exploration and exploitation within the context of a manufacturer's supply chain management strategy. Using survey‐based data gathered from 174 U.S. manufacturers, we find that an ambidextrous supply chain strategy coincides with combinative competitive capabilities and business performance. Our empirical finding contradicts conventional wisdom that argues for tradeoffs between exploration and exploitation. Instead, our empirical results are in line with an emerging complementarity view advocating that supply chain managers build practices to gain operational efficiency while simultaneously searching for opportunities to gain operational advantages. In addition, we provide insights regarding the role of combinative capabilities in mediating the relationship between an ambidextrous supply chain strategy and business performance.